INISIASI MENYUSU DINI MENJAGA KESTABILAN SUHU PADA BAYI BARU LAHIR - Nuli Nuryanti Zulala; Mei Neni Sitaresmi; Sulistyaningsih (MEDIA ILMU KESEHATAN, 2018)
Background: Hypothermia contributes 6.3% to neonatal mortality. Interventions to keep newborns warm can reduce neonatal mortality by 18-42%. Early Breastfeeding Initiation (EBI) is a simple intervention that reduces the risk of neonatal death. Objective: The aim of this study to determine the difference of axillary temperature of newborn between improper EBI group and proper EBI group for 24 hours. Methods: This prospective cohort study was conducted at Aisyiyah Muntilan Hospital. Sixty-two healthy newborns from healthy mothers born in November 2016 who meet the inclusion and exclusion criteria. Subjects were grouped in improper EBI groups (n=32) and proper EBI groups (n=32). Axila temperature measurements were performed at 1st minute, 30th minute, 60th minute, 6th hour, 12th hour, 24th hour. Results: The result of the hypotermic occurrence is more happened on improper EBI than proper EBI. EBI is able to prevent hypothermia during the first 24 hours of newborn life Conclussions: Infants with proper EBI have a lower risk of hypothermia. Keyword: Early Breastfeeding Initiation, Hypothermia, Newborn